Respuesta :

Answer:

see explanation

Step-by-step explanation:

CY = CB + BY

     = 6b + 5a - b

     = 5a + 5b

---------------------

CX = CA + AX

     = CA + [tex]\frac{1}{3}[/tex] AB , find AB

AB = AC + CB

     = - 3a + 6b

     = 6b - 3a

Thus

CX = CA  + [tex]\frac{1}{3}[/tex] AB

      = 3a + [tex]\frac{1}{3}[/tex](6b - 3a)

      = 3a + 2b - a

      = 2a + 2b

---------------------

and

[tex]\frac{2}{5}[/tex] CY

= [tex]\frac{2}{5}[/tex] (5a + 5b)

= 2a + 2b = CX

Hence CX = [tex]\frac{2}{5}[/tex] CY ⇒ Proven

 

ACCESS MORE